Analysis using multiple free space optic channel with amplification to mitigate haze attenuation - A.A. Anis; C.B.M. Rashidi; S.A. Aljunid (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Weather severity has unfavorable effect on FSO transmission performance. The impact could result in poor quality of transmission and communication failure. This paper presents the analysis using multiple free space optic channels with amplification to mitigate haze attenuation. The visibility is progressively reduced due to the attenuation effects, causing the bit error rate to increase. Three designs of FSO system are proposed in this research as they are simulated and analysed thoroughly using Optisys software. The achieved result shows improved performance for Design 3, as the minimum BER achieved is 10-127 when the power received is -26 dBm, and maximum Q-factor of 23.6 at the aperture diameter of 40 cm. It is proved to improve the system efficiently in low visibility condition compared to Design 1 and Design 2. It clearly has shown the superior capabilities of Design 3 to intercept and mitigate the atmospheric attenuation in haze condition as the power loss during transmission also reduced significantly.